Late Diagnosis of NBEAL2-related Gray Platelet Syndrome in Finnish Siblings with Lifelong Thrombocytopenia - Boeckelmann, Doris; Friman, Terhi; Glonnegger, Hannah; Wartiovaara-Kautto, Ulla; Zieger, Barbara (Hämostaseologie, 2025)
In the case of familial thrombocytopenia, a congenital defect should be considered; however, in particular older patients who have had thrombocytopenia for a long time have often not yet been genetically analyzed using modern sequencing methods. Remarkably, sometimes they are still suspected of suffering from chronic immune thrombocytopenia until genetic testing reveals a congenital defect. We report on elderly Finnish siblings (both older than 60 years) with lifelong thrombocytopenia. The lifelong bleeding tendency in both the siblings was usually treated with tranexamic acid and platelet transfusions when necessary. In 2022, the older brother presented at the University Hospital in Helsinki because he had recently been suffering from gastrointestinal bleeding and also had mild pancytopenia. Because his sister lived abroad, the Finnish colleagues recommended that the sister should present to the University Hospital in Freiburg. Independent genetic testing of both the siblings using NGS identified the diagnosis of NBEAL2-associated gray platelet syndrome. The disease comprises macrothrombocytopenia and a reduction of α-granules in platelets, resulting in a grayish appearance of platelets on the blood smear. Patients usually suffer from a mild to moderate bleeding diathesis. Interestingly, during the last years a more syndromic character of the disease has been described: besides the platelet phenotype, the immune system can also be affected. In the course of the disease patients may develop pancytopenia, splenomegaly, and bone marrow fibrosis. Comprehensive diagnostics including molecular genetic analyses are particularly important to provide these patients with adequate care and treatment.
Keywords: platelet disorder; congenital thrombocytopenia; gray platelet syndrome; NBEAL2; α storage pool disease